Genome-wide characterization of soybean RALF genes and their expression responses to Fusarium oxysporum - Liu, Yuhan; Chen, Yuhui; Jiang, Hengke; Shui, Zhaowei; Zhong, Yujun; Shang, Jing; Yang, Hui; Sun, Xin; Du, Junbo (Frontiers in Plant Science, 2022)
RALF is a kind of small peptide, which is very important for plant growth, development and immune response. In recent years, RALF has been found to regulate plant resistance to fungal infection. However, little is known about crops, especially soybean. Here, 27 RALFs in Glycine max (GmRALFs) were identified in the genome. All GmRALFs from soybean and 34 AtRALFs from Arabidopsis, a total of 61 genes, were divided into 12 clades according to the phylogenetic analyses. Gene structures, conserved motifs, chromosome distribution, and cis-elements were analyzed in the present study. Furthermore, 18 GmRALFs were found to respond to Fusarium oxysporum infection in soybean, and exhibit different expression patterns. Some GmRALFs have a secretory function. Our current study systematically identified and characterized GmRALFs in the soybean genome and laid a foundation for further functional analyses and soybean breeding.